URGENSI KAJIAN KEISLAMAN DENGAN PENDEKATAN MULTIDISIPLINER DALAM MENGHADAPI ISU-ISU KONTEMPORER - Sholikah Sholikah; Nurotun Mumtahanah; Ahmad Hanif Fahruddin (Akademika, 2022)
Nowadays, the fundamental problem is the growing tradition of Islamic thought, which is accepted dogmatically. This causes the closure of creativity and innovation to develop these traditions under the human experience development so that contemporary issues are not resolved. Therefore, it is necessary to have a critical methodology that uses a multidisciplinary approach, namely understanding Islam using various scientific disciplines, including philosophy of science, socio-social science, and natural sciences (science). With this multidisciplinary approach, Islamic studies are expected to accept criticism from various parties, both insiders and outsiders. An Islamic civilization that is cosmopolitan, full of love, tolerant, and upholds pluralism, human rights, and women's dignity will be realized.